Application of Technology in Educational Management in Rural Schools - Pradana, Muhammad Rafieq Adi; Josiah, Trisnowati (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2024)
This study aimed to evaluate the application of technology in educational management in rural schools, focusing on infrastructure challenges, teacher readiness, digital resource integration, and their impact on academic outcomes. Using a qualitative research approach, we analyzed secondary data from various rural schools across Indonesia. Thematic analysis was employed to identify recurring themes and patterns. The findings revealed significant infrastructure barriers, including unreliable internet connectivity, insufficient digital devices, and inconsistent electricity supply. Teacher readiness emerged as a critical factor, with many educators lacking the necessary skills and confidence to integrate digital tools effectively. Despite these challenges, the successful integration of technology in some schools led to improved student engagement and learning outcomes. The study underscores the need for targeted investments in infrastructure and comprehensive professional development programs to equip teachers with digital competencies. Addressing these barriers is essential to harness the benefits of technology, reduce disparities between urban and rural education, and improve overall educational outcomes. The research contributes valuable insights and recommendations for policy interventions and future research in the context of rural education.